PENGGUNAAN INTERNET BERBASIS GADGET UNTUK MENINGKATKAN KEMANDIRIAN, MOTIVASI DAN HASIL BELAJAR SISWA KELAS V - Yosepha Armiyati; Hairida Hairida; Antonius Totok Priyadi (Universitas Tanjungpura, 2021)
Abstract This study to explain the increase in learning independence, learning motivation and learning outcomes in science learning through the use of gadget based internet for fifth grade students. This research is a classroom action research conducted at 01 kubu public elementary school. Number of subjects were 25 students. Data collection was carried out using observation sheet, test questions, questionnaires, and documentation. Based on the results of research and data analysis, it shows that the use of gadget-based internet can improve learning independence, learning motivation, and student learning outcomes in science learning. The increase in student learning independence can be seen from the first cycle as much as 16%, second cycle 36%, and third cycle students who have high learning independence again increased to 60%. The increase of student learning motivation can be seen from the first cycle as much as 36%, second cycle 48%, and third cycle students who have high learning motivation again increased to 64%. The increase in student learning outcomes can be seen from the first cycle, it was obtained that 60% had reached learning standard, second cycle 76% had reached learning standard, and third cycle 88% had reached learning standard. Keywords: Internet, Gadgets, Learning independence, Learning motivation, Learning outcomes.